Seropositive Rate and Associated Factors of Schistosomiasis in Hunan Province, China: A Three-Year Cross-Sectional Survey - Xu, Lingqi; Zhou, Yu; Tang, Ling; Hu, Benjiao; Zhu, Liyun; Gong, Yanfeng; Shi, Liang; Huang, Junhui; Wang, Jiamin; Xu, Ning; Chen, Yue; Jiang, Qingwu; et al. (Acta parasitologica, 2025)
Introduction China’s Hunan Province, known for its extensive lake and marshland areas, continues to face considerable challenges in eliminating schistosomiasis. This study aims to examine the epidemiological characteristics of schistosomiasis in the province, focusing on seropositive rates across various demographic groups, spatial distribution, and identifying key associated factors to inform targeted control measures. Methods From 2020 to 2022, the number of people screened each year using the indirect hemagglutination assay (IHA) was 1,053,973, 682,921, and 729,782, respectively. The Cochran-Armitage test for trend and chi-square test were employed to assess differences in seropositive rates among different times, age groups, genders, educational levels, and occupations. Spatial autocorrelation analysis was conducted to identify clusters of seropositive rates at the village level. A multiple logistic model was used to identify associated factors and generalized estimating equation (GEE) was used to obtain the parameter estimates. Results From 2020 to 2022, the seropositive rate of schistosomiasis in Hunan Province were 1.53% (95% CI: 1.51–1.55), 2.22% (95% CI: 2.19–2.26), and 2.06% (95% CI: 2.03–2.10), respectively. The seropositive rate in Hunan Province was spatially clustered in each year, with high-high clustering areas mainly distributed around the southern Dongting Lake region, the tributary areas of Dongting Lake, as well as along the Yangtze River. The seropositive rate increased with age, with individuals aged 60–69 showing the highest seropositive rate (adjusted odds ratio [OR] when compared to < 10 years old: 47.94; 95% CI: 30.04–76.52). Males had higher seropositive rate compared to females (adjusted OR: 1.72; 95% CI: 1.69–1.76). Compared to farmers, fishermen (adjusted OR: 2.54; 95% CI: 2.40–2.70) and business/service staff (adjusted OR: 1.63; 95% CI: 1.52–1.74) had higher seropositive rate. The seropositive rate decreased with increasing educational level. Individuals using tap water and sanitary toilets had lower seropositive rate compared to those who did not use (tap water: adjusted OR: 0.66; 95% CI: 0.64–0.68; sanitary toilets: adjusted OR: 0.95; 95% CI: 0.93–0.97). Additionally, those who raised sheep had a higher seropositive rate compared to those who did not (adjusted OR: 4.67; 95% CI: 4.04–5.39). Conclusions Schistosomiasis remains a significant public health issue in Hunan Province, with the seropositive rate remaining clustered in certain regions and high-risk populations. Achieving schistosomiasis elimination requires sustained targeted interventions, improved sanitation infrastructure, enhanced health education, and long-term monitoring and comprehensive control measures for high-risk areas and vulnerable populations to reduce transmission risk and ensure sustainable disease elimination.